Bound lipase: an important form of lipase in rice bran (Oryza sativa) - Chengwei Yu; Bin Peng; Ting Luo; Zeyuan Deng (Food Science and Human Wellness)
Rice bran residue possessed a steady lipase activity ((26.68 ± 3.69)%) after its endogenous lipase was extracted continuously by phosphate buffer solution (PBS) for 24 h. Therefore, the aim of this research was to explore whether there exist any bound lipases in rice bran (Oryza sativa). Three physical treatments (grinding, homogenizing and ultrasound crush) and 6 enzymatic treatments (cellulase, hemicellulase, pectinase, complex cellulase, glucoamylase and α-amylase) were applied to rice bran in order to investigate this bound lipase. The relative catalytic activities of extraction supernatant and residue for pectinase group were (437.63 ± 22.54)% and (159.26 ± 2.12)%, respectively, which were significantly higher (P < 0.05) than other groups. This phenomenon demonstrated that lipase was the most likely to combine with pectin. Molecular simulation proved that pectin could combine with two rice bran lipases (lipase 315 and lipase 308) and cover the catalytic centers so as to prevent the lipases from encountering the substrate and inhibiting their catalytic activities. During combination, pectin could make the lipases more compact and reduce the solvent accessible surface area of lipases, which would make the lipases inactive to molecular interaction. In summary, part of rice bran lipase was proved to exist in bound form and combined with the pectin.